Desmistificando a teoria da relatividade de Einstein - Almeida, Fábio Jardim de (2022)
We present in this work the ideas that support Einstein’s theory of relativity and an account of the historical development of non-Euclidean geometries. We also list some applications of the theory of relativity and organize activities/experiments for students to experience concepts of this theory – the value of the speed of light and its invariance – and spherical geometry – the area of terrestrial surfaces with Google Earth. We conclude that technological resources are essential to fully understand the physical and mathematical concepts that underlie the theory of relativity and non-Euclidean geometries.